A knowledge-based system for low-grade waste heat recovery in the process industries. (5th February 2016) - Law, Richard; Harvey, Adam; Reay, David
Highlights: A knowledge-based system has been developed. System database includes heat exchangers, heat pumps and organic Rankine cycles. System results include technical, economic and environmental considerations. A case-study is shown, highlighting successful demonstration of the system. Abstract: The rising cost of energy, combined with increasingly stringent legislation to reduce greenhouse gas emissions is driving the UK process industries towards increasing energy efficiency. Significant gains can be made in this sector by recovering low-grade waste heat as up to 14 TWh per annum (4% of total energy use) of the UK process industries' energy consumption is lost as recoverable waste heat. Substantial recovery of this would have economic benefits of the order of £100s of million/year and environmental benefits of 100s of thousands of tonnes of carbon dioxide equivalent per year. A similar situation is envisaged in other industrialised countries. This paper describes the development of a knowledge-based system for the selection and preliminary design of equipment for low-grade waste heat recovery in the process industries. The system processes commonly available plant data to select the most appropriate technology for waste heat recovery from a range of programmed options. Case-study testing shows that the system can successfully select and design viable solutions for waste heat recovery from a range of options, producing designs which are economically, environmentally and technically feasible.